Optimization of geometric forms for urban transport stops/Visuomeninio transporto stotelių racionalių geometrinių formių nustatymas - Rimkus, Aleksas (Journal of Civil Engineering and Management, 1999)
In order to improve the functioning of urban transport it is necessary to increase the efficiency of intermediate stops and organization of municipal transport service. There are two ways of solving problems of developing urban transport: 1) to install special lanes in the streets for urban transport only and 2) to improve the geometric forms of the existing stops arranging stop “pockets”. The first way requires a lot of investments. The second is more preferable. It allows a safe and efficient use of vehicles, an increase in stop usage intensity. Therefore it may be considered the most important means for developing passenger transport. The experimental investigations have shown that stop pockets should be of 4 m width. Such pockets diminish considerably the number of conflict situations and troubles with transport vehicles driving along the first and second lanes and ensure for passengers the possibilities of getting comfortably and safely on a vehicle. An abrupt braking of a bus or trolley-bus before a stop or in its area affects in an unpleasant way the passengers, causes dangerous situations, transport vehicles are sometimes damaged and shear stresses result in street covering deformations. It was established that deceleration and acceleration lengths depend on a vehicle speed influenced by deceleration and acceleration value a = 1,2 m/s2. The length of deceleration and acceleration is from 30 to 116 m. It has been found by an analysis for tracks of public transport vehicles entering and leaving the stop pockets that they do not enter a stop pocket by a radius arc but by a varying curve. The shape of such a curve depends on drivers' professional skills, vehicle technical parameters and speed. In accordance with experiments and calculations, data and formulas were obtained for detailed coordinates of stop pockets. Geometric forms and parameters of stop pockets were established. Regarding the geometric shape of stop pockets, the entering speed of vehicles and their plans as initial parameters, the dimensional values of stop pocket elements were differentiated according to categories of streets and their disposition in relation to crossings (Table 4.2). The calculations have shown that investments into stop pocket development are profitable in many aspects: the entire area of a stop pocket is used, the traffic safety and duration of street coverings are increased, no traffic jams occur before the stop, the passenger servicing and municipal transport maintenance are improved. The expenses for installing a stop pocket in repaid in 0,49 of a year.Article in Lithuanian.First Published Online: 26 Jul 2012